Resistensi dan karakter molekuler benih gurami sowang Osphronemus goramy Lacepede, 1801 asal induk berbeda - Kusbiyanto Kusbiyanto; Agus Nuryanto; Petrus H. T. Soedibja (Depik, 2017)
The cultivation of giant gourami is constrained by its high mortality due to low resistance to diseases. Resistance is an inherited character from the parental to their seeds. High resistance seeds can be selected using molecular marker, such as Major Histocompatibility complex (MHC) gene. Resistance character is assumed to be different among individual from different broodstocks and is suggested related to their genetic constituent.  This research aims to analyze the resistance of sowang gouramy seeds from different broodstocks and describe genetic character of seeds from different broodstocks. An explorative survey was perfomed. One hundred individuals were taken purposively from Balai Benih Ikan Sikamaju Ciamis West Java and hundred individuals were bought from fish farmer in Ciamis West Java. Sampling was performed in 2015 for the first seed group and in 2016 for the second seed group. Samples were subjected to Aeromonas hydrophila and Pseudomonas aeruginosa infection. The fragments of MHC gene were amplified using PCR technique from eight individual of first group and six individuals of second group. The resistance characteristic was analyzed using simple mathematics based on the number of living seeds compared total infected seeds and molecular characteristics was analyzed descriptively based on DNA band pattern. Different resistance to A. hydrophila was observed between seed groups from different broodstocks. The seeds group from the first broodstocks showed lower resistance level with the value of 29% than that from the second broodstocks with the resistance value reached of 100%. Both seed groups also showed resistance differences to P.aeruginosa, although  not as high as A.hydrophila infection. The differencies were also reflected in their MHC gene between seed groups from two different broodstocks. The amplication of MHC gene of the seeds from the first broodstacks resulted of 585 bp and 400 bp length fragments, while from those second broodstocks was only resulted of 400 bp frament. The differences on DNA band pattern between seed groups indicate a different molecular characteristics among seeds from different broodstocks.Usaha budidaya ikan gurami terhambat oleh tingginya mortalitas benih karena rendahnya resistensi terhadap penyakit. Resistensi merupakan sifat yang diwariskan dari tetua ke anakan. Benih yang resisten dapat diseleksimenggunakan marka molekuler seperti gen Major Histocompatibility complex (MHC). Sifat resisten diduga berbeda diantara benih yang beraasal dari induk berbeda dan diduga terkait dengan kompenen genetik yang dimiliki. Tujuan penelitian ini adalah untuk mengetahui sifat reisten dan karakter molekuler benih gurami sowang asal induk berbeda. Fragmen gen MHC diamplifikasimenggunakan teknik PCR. Sifat resistensi dianalisis menggunakan perhitungan matematika sederhana berdasarkan jumlah benih hidup dibagi jumlah total benih yang diinfeksi, sedangkan karakter molekuler dianalisis secara deskritif berdasakan pola pita yang dihasilkan. Kedua kelompok benih memiliki sifat resistensi berbeda terhadap Aeromonas hydrophila. Benih dari induk pertama memiliki sifat resistensi lebih rendah dengan nilai kelangsungan hidup sebesar 29% daripada kelompok benih dari induk kedua yang memiliki kelangsungan hidup mencapai 100%. Kedua kelompok benih juga memperlihatkan perbedaan sifat resisten terhadap P. aeruginosa, meskipun perbedaannya tidak sebesar terhadap A.hydrophila. Perbedaan tersebut juga tercermin pada gen MHC kedua kelompok benih. Pada kelompok benih pertama dihasilkan dua fragmen gen MHC dengan ukuran 585 pb dan 400 pb, sedangkan dari kelompok benih kedua hanya dihasilkan fragmen berukeuran 400 pb. Perbedaan pola pita diantara kedua kelompok benih tersebut merupakan idikasi adanya perbedaan karakter molekuler pada benih yang berasal dari dua induk berbeda